O sagrado na poesia de Dora Ferreira da Silva - Bittencourt, Amanda Rosa de (2016)
Dora Ferreira da Silva, a poet from São Paulo, has a vast work: nine books published during her lifetime, three works published posthumously, in addition to her respected work as an essayist and translator. She received the Jabuti Award three times and one time the Machado de Assis Award, promoted by the Academia Brasileira de Letras. This research comes to revitalize the concept of the sacred and its developments in a corpus of nine poems of the poet, through the understanding of studies that aims the Theories of the Sacred, from Rudolf Otto, Mircea Eliade, Jacques Wunenburger and Joseph Campbell, the Theory of the Imaginary of Gilbert Durand and Gaston Bachelard, the Analytical Psychology of Carl Gustav Jung - which Dora was one of the translators -, and the Theories of Literature of Octavio Paz and Northop Frye. The literary work recreates the symbolism of sacred manifestations, giving them a new perspective related to the subject of the unconscious. This dissertation points to the fascination that the issues relating to the sacred creates within the poetic activity that links to the archetypal richness of ancient myths and their rites, and so for these artistic hierophanies establishes a dialogue with the unknowable and ineffable of the human experience. The writer herself says in an interview: "Giving the little that you have, be true to your inner voice, it is what is asked from poets in an attempt to meet this need of the gods".